Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Student Teams Achievement Division (STAD) Pada Materi Sistem Pernapasan Manusia Kelas XI SMAN 1 Labuhan Deli T.A. 2022/2023 - Adelia Putri; Wasis Wuyung Wisnu Brata (International Forum of Researchers and Lecturers, 2023)
This study aims to design and produce Student Worksheets (LKPD) based on the Student Teams Achievement Division (STAD) on class XI human respiratory system material. This type of research is Research and Development (Reasearch & Development) with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The subjects of this study were 2 material expert validator lecturers and 2 learning expert validator lecturers, the assessment of 1 biology teacher, and the responses of class XI MIPA-3 students of SMAN 1 Labuhan Deli T.A. 2022/2023. Data analysis used quantitative and qualitative descriptive analysis. The results showed that the development of STAD-based LKPD obtained validation results by material experts of 96.88% in the